Managing Fusarium wilt of bananas with endophytic microorganisms - Ting, Adeline Su Yien; Meon, Sariah; Radu, Son; Kadir, Jugah; Singh, Gurmit (Penerbit Universiti Sains Malaysia, 2004)
Fusarium wilt of banana is a common disease in many banana growing countries worldwide. Attempts to control this disease using cultural practices, chemical application and breeding for resistant varieties, has met with little success. The pathogen, Fusarium oxysporum f. sp. cubense (Foc) spends part of its life cycle in the host tissues, thus ‘escaping’ the effect of control applications.